Perjanjian Sewa Menyewa Sound System untuk Keperluan Resepsi di Kelurahan Lokea Kecamatan Larantuka Kabupaten Flores Timur Ditinjau dari Hukum Perdata - Kamlasi, Yoseph Mariano; Hedewata, Agustinus; Dinata, Husni Kusuma (Information Technology and Science (ITScience), 2024)
The need for the community for reception purposes is increasing, so people are starting to think about running a business, namely renting moving goods for reception purposes and one of them is a sound system. In doing a lease, of course, there is an agreement between the tenant and the renter, both an oral and written agreement. This study used empirical research methods. This research was conducted by data collection techniques, namely, interviews and document studies. Data that have been collected both through interviews and document studies, analyzed descriptively-qualitatively. The results of this study show that: (1) The implementation of the sound system rental agreement for reception purposes in Lokea Village is usually carried out orally and does not have many requirements and only relies on trust between related parties. In general, the tenant of the sound system for reception purposes in Lokea Village is from the bride's side, because of the custom of the Lokea community the reception will be held on the bride's side. (2) Obstacles from parties involved in this sound system rental agreement include trust factors, quality of goods rented, negligence on the part of the tenant and return of goods that exceed the term of the rental agreement. (3) The rights and obligations of the parties to this sound system rental agreement are that the lessee has the right to receive rent, receive compensation, and decide to whom this item will be rented, in addition to the lessee also Obliged to guarantee that the rented goods are in good condition for use and are obliged to install. The tenant has the right to use the rented item according to the agreement and is entitled to receive compensation in the form of a discount, besides that the tenant is also obliged to pay the rental price and maintain the rented item.